Program transformasi OKU melalui edu-tourism: satu tinjauan terhadap kompetensi keusahawanan orang kelainan upaya (OKU) - Abdullah, Syahrina; Mohamad, Armanurah; Abu Bakar, Lily Julienti (2016)
This study focused on the transformation of entrepreneurship knowledge from the aspect of self competency among disable people who were participated in Transformation of Disable People through the Edu-Tourism Program. The opportunity to gain entrepreneurial knowledge from self-competency aspect would give self motivation to disable people as well as it can contribute to country development agenda in entrepreneurship field. This program involved transferring knowledge from academia to industry and then the industry will transfer the knowledge to the participants of this program. Transformation of Disable People through the Edu-Tourism Program was a joint program between UUM, EMKAY Foundation and Pulau Banding Foundation. There were ten participants of disable people in this program. The objective of this study was to explore level of self competencies among the participants of disable people. The study showed that the overall mean score in identifying entrepreneurial competencies among disable people had risen from a moderate low level (mean score of 2.10) to a moderate high level (mean score of 3.2) after they participated in the program. Thus, the program can motivate disable people to involve in entrepreneurship field for their future.